Tinjauan Pengaruh Beban Berlebih Terhadap Pengurangan Umur Rencana Perkerasan Jalan pada Ruas Jalan A.Y. Patty, Kota Ambon - Eka S. Marasabessy; Hamkah; Sulastri Kakaly (PT Bukuloka Literasi Bangsa, 2026)
Traffic growth and overloaded vehicles increase the cumulative axle loading received by pavement and may accelerate the reduction of road service life. This study aims to analyze the effect of excessive vehicle loading on the reduction of flexible pavement design life along A.Y. Patty Road STA 000+000–000+400, Ambon City. A quantitative descriptive approach was applied. Primary data were obtained through Average Daily Traffic surveys and pavement condition observations conducted on 6, 9, 10, and 11 August 2025. Secondary data consisted of the existing pavement structure, road network maps, and technical data from the Ambon City Public Works and Spatial Planning Agency. The analysis included vehicle classification and calculations of the Vehicle Damage Factor, Equivalent Single Axle Load, and Cumulative Equivalent Standard Axle Load, followed by traffic growth simulations of 5%, 10%, and 15% based on the 2024 Indonesian Pavement Design Manual. The results show that heavy vehicles contributed the greatest pavement damage, with VDF values of 2.328545 for two-axle trucks and 4.5840272 for articulated trucks. At the end of the analysis period in 2034, cumulative ESAL reached 1,674,841.38 under the 5% scenario, 2,664,367.80 under the 10% scenario, and 11,793,313.88 under the 15% scenario. The differences in remaining pavement life compared with the planned condition reached 5%, 10%, and 15%, respectively. Therefore, higher traffic growth and vehicle loading accelerate the consumption of pavement capacity and reduce its service life. Vehicle-load control and earlier maintenance are required to preserve road performance in accordance with the planned service life. Keywords: overloading, Equivalent Single Axle Load, Pavement Design Life.